2014
DOI: 10.1038/aps.2014.88
|View full text |Cite|
|
Sign up to set email alerts
|

Probucol suppresses human glioma cell proliferation in vitro via ROS production and LKB1-AMPK activation

Abstract: Aim: Probucol, an anti-hyperlipidemic drug, has been reported to exert antitumor activities at various stages of tumor initiation, promotion and progression. In this study we examined whether the drug affected glioma cell growth in vitro and the underlying mechanisms. Methods: Human glioma U87 and glioblastoma SF295 cell lines were used. Cell proliferation was accessed using the cell proliferation assay and BrdU incorporation. The phosphorylation of AMPK, liver kinase B1 (LKB1) and p27 Kip1 was detected by Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…In addition, probucol was shown to possess anti-inflammatory, anti-fibrotic, and anti-oxidative effects [ 23 , 24 ] to delay the progress of early diabetic nephropathy [ 23 , 25 ]. Jiang et al [ 26 ] showed that probucol markedly increased the ROS production and inhibited lipoprotein lipid oxidation. Moreover, in a diabetic nephropathy model, probucol significantly reduced MDA levels, enhanced GSH-Px activity, and reduced glomerular pathological changes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, probucol was shown to possess anti-inflammatory, anti-fibrotic, and anti-oxidative effects [ 23 , 24 ] to delay the progress of early diabetic nephropathy [ 23 , 25 ]. Jiang et al [ 26 ] showed that probucol markedly increased the ROS production and inhibited lipoprotein lipid oxidation. Moreover, in a diabetic nephropathy model, probucol significantly reduced MDA levels, enhanced GSH-Px activity, and reduced glomerular pathological changes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…ROS are also able to inhibit LKB1-mediated activation of AMPK, alleviating mTOR inhibition and promoting entry into the cell-cycle and glioma proliferation in vitro (Jiang et al, 2014). Downstream of AMPK, PGC-1α controls transcription of antioxidative proteins alongside mitochondrial biogenesis, highlighting the tight control of ROS in response to increased mitochondrial respiration (Hartel et al, 2016).…”
Section: Reactive Oxygen Species and Redox Homeostasismentioning
confidence: 99%
“…Mutations in the tumor suppressor LKB1 limit AMPK activity and the production of NADPH through catabolic processes; unrestrained ROS can promote tumor growth by boosting oncogenic signal transduction, genetic instability and glioma growth in vivo (Jeon et al, 2012 ). ROS are also able to inhibit LKB1-mediated activation of AMPK, alleviating mTOR inhibition and promoting entry into the cell-cycle and glioma proliferation in vitro (Jiang et al, 2014 ). Downstream of AMPK, PGC-1α controls transcription of antioxidative proteins alongside mitochondrial biogenesis, highlighting the tight control of ROS in response to increased mitochondrial respiration (Hartel et al, 2016 ).…”
Section: Reactive Oxygen Species and Redox Homeostasismentioning
confidence: 99%
“…AMP-activated protein kinase (AMPK) is a key regulator of energy metabolism [ 7 ] by activating the synthesis of fatty acid, cholesterol, protein through phosphorylation of metabolic enzymes and ATP-generating processes, including glucose uptake [ 8 ]. A tumor suppressor liver kinase B1 (LKB1) is its upstream kinase that phosphorylates and activates AMPK signaling by encoding serine/threonine kinase [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%